VARIOUS DIMENSIONS OF RAJASTHANI PAINTING - Shrivastava, Salil (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The above research paper is an attempt to explain the various styles of Rajasthani painting on historical and artistic basis. It starts from the oldest known painting from the 10th century, Odh Niryukti Vritti and Das Vakalika Sutra Churni, and passes through various regional styles of Rajasthan to the present modern painting style. It attempts to explain the various art styles of Rajasthan which originate from Mewar and how they spread to other regions like Bundi, Jaipur etc. and at what levels they display their regional variations. The above study explains its following functions in the form of explaining the relationship between the regional culture of Rajasthan and their pictorial expressions.